2011
DOI: 10.1111/j.1464-410x.2011.10127.x
|View full text |Cite
|
Sign up to set email alerts
|

Androgen deprivation therapy in prostate cancer: are rising concerns leading to falling use?

Abstract: Study Type – Therapy (cohort) Level of Evidence 2b What’s known on the subject? and What does the study add? Androgen deprivation therapy was originally used for metastatic prostate cancer but is now used to treat all stages of the disease. Once considered to be relatively harmless, androgen deprivation therapy was associated with impaired cognitive function, anemia, loss of muscle strength, osteoporotic fractures, diabetes, and cardiovascular disease by the year 2000. In a large, population‐based sample of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 49 publications
1
15
1
Order By: Relevance
“…3,4 A SEER analysis found that use of ADT increased throughout the 1990’s followed by decline leading up to 2005 5 . A population-based study in Canada found similar patterns 6 . These declines in ADT usage may be related to toxicity concerns.…”
Section: How Should Androgen Deprivation Be Added To Definitive Radiamentioning
confidence: 81%
“…3,4 A SEER analysis found that use of ADT increased throughout the 1990’s followed by decline leading up to 2005 5 . A population-based study in Canada found similar patterns 6 . These declines in ADT usage may be related to toxicity concerns.…”
Section: How Should Androgen Deprivation Be Added To Definitive Radiamentioning
confidence: 81%
“…Treatment with orchiectomy has declined in recent years 3,6 , and the indications for which it is relevant are few. We therefore included only patients who received orchiectomy for metastatic disease or as primary therapy, and those who received cab-surgical for metastatic disease.…”
Section: Adt Regimens and Indicationsmentioning
confidence: 99%
“…Many patients receive androgen deprivation therapy (adt) as primary therapy for all stages of disease or in addition to primary surgery or radiotherapy [2][3][4][5] . Luteinizing hormone-releasing hormone (lhrh) agonists and anti-androgens are now the main types of adt; bilateral orchiectomy and estrogen are less popular [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%